Streptococcus gallolyticus infection: A neglected marker for colorectal cancer? - Ismail, Che Muhammad Khairul Hisyam; Mohammad Aidid, Edre; Hamzah, Hairul Aini; Shalihin, Mohd Shaiful Ehsan; Md Nor, Azmi (Elsevier, 2023)
Background and study aims Colorectal cancer (CRC) is the second most common cancer in Malaysia and mostly detected at advanced stages due to lack of awareness of CRC symptoms and signs. CRC pathogenesis is multifactorial, and there is ambiguous evidence on association of Streptococcus gallolyticus infection with CRC that needs further attention.